Karakterisasi Mikroflora Alami Saluran Pencernaan Sapi Potong Sebagai Kandidat Probiotik Pakan Sapi Potong - Uswatul Hasana; Nurmiati Nurmiati; Periadnadi Periadnadi (Jurnal Biologi Universitas Andalas, 2013)
The research about the "Characterization of Natural Microflora From Cow Digestic Tract As Candidate For Cattle Feed Probiotics"  has been conducted from April to July 2013 in the Laboratory of Microbiology, Department of Biology, Faculty of Mathematics and Natural Sciences, University of Andalas, Padang. This study aimed to obtain isolates  and the character of each isolate as a candidate to cattle feed probiotics. This study used an experimental method and analyzed descriptively. The result showed that the bacteria from cow digestive tract were Cellulolytic (110x107cfu/g), Fermentative (85x107cfu/g),  Amylolytic (31x107cfu/g) and Proteolytic (28x107cfu/g) bacteria. Two of  the probiotic candidate were bacill and coccus, both of them were Gram-negative and catalase positive.